Evaluation of wheat based mixed cropping in river-basin areas of western Nepal - Pokharel, Bhanu Bhakta; Sharma, Shashi Ram; Pun, Gam Bahadur; Chhetri, Naina Singh (Journal of Cereal Research, 2017)
Growing of oilseeds, rapeseed and winter legumes like lentil, pea and gram as mixed crop with wheat are common practice in Nepal. Field experiment was conducted to find out the optimum seed rate of wheat as well as mixed crops appropriate for wheat based mixed cropping in the region. Field experiment was conducted during the winter seasons of 2010-11 and 2011-12 in the river basin region of Surkhet district in randomized complete block design with three replications. These mixed crops were broadcasted together with wheat at the same time and the same field. Chemical fertilizer was applied at the rate of 100:40:30 kg NPK/ha and no additional fertilizers were supplied to the mixed crops. The sole wheat yielded (4,877 kg/ha) and seed rate combination of lentil or pea (30 %) + wheat (70 %) recorded maximum wheat equivalent yield in these crop combinations. Similarly, seed rate combination of gram (40 %) +wheat (60 %) and toria (20 %) + wheat (80 %) produced higher wheat equivalent yield in respective crop combinations. DOI:10.25174/2249-4065/2017/71985